A Pharmaceutical Logistics still far from answering health concerns of the country: budgetary weaknesses - N'weti (N'weti, 2020)
Key Messages: - Pharmaceutical logistics make up only 7% of total projected costs for the health sector through 2019; - The expansion and demand of the health sector in the forthcoming years will not be accompanied by the necessary increase in resources for the pharmaceutical logistics sector; - Increased nancing in the area of PL is necessary, preferably from internal sources, to allow the implementation of PELF recommendations; - It is estimated that 13% of the value of the approximately $3,929 million needed to procure and manage drugs and commodities during 2014-2019 will be wasted. - The health sector is heavily reliant on external funding, with 81% of funding for medicines comming from external partners; - There is concerning public evidence of systematic stock-outs of medicines in public pharmacies throughout the country. Research by Nweti (2014-2015) in 37 health acilities in four provinces using the community score card as a survey tool, found that stock-out of essential medicines was one of the barriers to accessing quality health services. Another study carried out by Wagenaar, et al. (2014) in Sofala Province, which assessed 26 facilities showed that only one out of the 26 facilities assessed in 2011, 2012, and 2013 had all of the 15 essential medicines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; health / saúde